Estudo sobre linguagem oral e escrita em adolescentes infratores institucionalizados - Destro, Carla Maria Ariano (2011)
Introduction: Juvenile delinquency, associated with complex social consequences, has received research and studies, extending across the various fields of social sciences and humanities. The difficulties in school adjustment, learning, may also be related to language disorders, which can lead to cognitive and linguistic limitations, contributing to social maladjustment and behavior of young offenders. Objective: To map and characterize the occurrence of disturbances of oral and / or writing in a group of institutionalized juvenile offenders, checking possible impacts of language difficulties and communication in the social life of these subjects. Method: This project sets an exploratory and descriptive study, which estimates the occurrence and features communicative difficulties (oral and written) in a group of young offenders institutions. The research subjects were 40 internal Fundação Casa, IU 25 unit - Rio Negro, from the complex of Franco da Rocha city - SP. The youths were aged between 15 and 18. To collect the data were applied the test Mini-Mental State Examination - MMSE, which aims to detect individuals who may have cognitive impairment; the Montreal test, which examined the abilities of each individual simple oral and written language, and a semi-structured interview, whose script was about General Health, School Path, Path Vocational and perceptions of criminal behavior. Results: The results showed that the majority of the population was literate and there was no occurrence of cognitive impairment. There was a high school dropout rate reported, arising from difficulties in following the school curriculum and to adapt to the rules and school dynamics. A significant percentage of subjects reported using drugs. Conclusion: This study leads us to reflect on problems that young offenders have in terms of integrating social conditions to develop and engage the values and socio-cultural norms, as well as schoolchildren, giving evidence, among other factors, the social impact that the poor education of young people can help bring. The study demonstrates that the language should be thought of as social practice. Self-esteem, difficulties in relating with others; to adapt and have good academic performance or to achieve stable occupation, exposed to these adolescents constraints, which tend to produce helplessness and anger at a delicate stage of development is adolescence, which creates difficulties in social adaptation, which may affect the language and, above all, forms of expression and communication of these subjects